Mode Choice And Service Integration Analysis To The Service Attributes Of Public Transportation At Kaliurang Street - Hidayat A M (International Conference on Engineering and Technology Development (ICETD), 2017)
Economic growth increases people’s mobility which results in the increase in the need of transportation infrastructure, exceeding current capacity. This research aims to identify the factors affecting citizen’s choice of service attributes of the proposed public transport along Kaliurang Street, to give service attribute scenario, and to analyze trip pattern and to analyze the service integration of public transport along Kaliurang Street. The route that will be used in this research starts from Ring Road Kentungan intersection and ends at Kaliurang Tourism Object. The data was analyzed using technical corelation and crosstabs technic. The significant factors obtained are: monthly income, trip urgency, passanger capacity, service intensity, the use of shelter, availability of AC and service integration. Service integration with Trans Jogja bus is located at CondongCatur bus station and Kentungan Intersection, and with using feeder service operating around Kaliurang Street